Keberdayaan Peternak Kambing melalui Aplikasi Teknologi Pakan Fermentasi Berbasis Limbah Pertanian (Jurnal Bina Desa, 2022)
Animal feed is only obtained from daily grazing without taking into account the needs of livestock. The problems that are often faced by farmers in dairy goat cultivation are the quality of the feed provided is still relatively low and commercial feed is expensive. This is due to fluctuations in the quality and quality of existing feed raw materials, especially from forages and legumes. Alternative feed from agricultural waste is not utilized because the knowledge of farmers regarding feed processing and improving feed nutrition is limited. The limitations of tools such as chopper machines used in chopping. Traditional maintenance and production costs that are not properly monitored, steps need to be taken to improve maintenance management and feed management to improve the welfare of farmers. Based on the results of the proposal team's analysis of the problems experienced by partners, in this year's service activities, the proposer team formulates solutions to overcome partner problems. The solution offered for partner problems is through the Triple Better Program theory by Patrick Boyle; informational through counseling partners about the potential of agricultural waste as fermented feed to increase the quality and quantity of livestock production, institutional through Training Activities for Partners on how to treat waste agriculture into fermented feed according to livestock needs, and training and counseling on group organization and good business management and developmental, namely monitoring the level of partner empowerment from an economic perspective.